Time-series transcriptomic analysis of flower tissue during heat stress in heat-resilient and heat-sensitive Brassica napus L. - Hu, Xiaojie; Chen, Sheng; Ping, Xiaoke; Siddique, Kadambot H. M.; Cowling, Wallace A. (Frontiers in Genetics, 2026)
Brassica napus a cool-season oilseed crop, is an important source of edible oil and biofuel. Heat stress during the reproductive stage poses a serious threat to its productivity, but little is known about the gene networks involved in the heat stress response during this phase. In this study, we conducted a time-series transcriptome analysis of heat-stress response in flowers and immature pods of four cultivars of B. napus to reveal heat-responsive gene pathways associated with heat sensitivity and resilience. Individual plants were moved to the heat stress or control treatments in the morning of the day when the flower opened at the second reproductive node of the main stem, defined as day zero after treatment (DAT0). Flowers at the second to fifth reproductive nodes on the main stem were collected in the afternoons of DAT0, DAT1, DAT3 and DAT6 of heat stress and control treatments for time-series transcriptome analysis. A total of 36,933 differentially expressed genes (DEGs) were identified in reproductive tissue under heat stress compared to the control treatment. In heat-resilient cultivar AV-Ruby, more than 4,000 unique DEGs were enriched in DNA repair and antioxidant defence pathways which support efficient stress recovery mechanisms and enhanced protection against oxidative damage in flower and immature pods tissue. Three heat shock proteins were upregulated under heat stress in all four cultivars of B. napus from fertilisation to early embryo and seed development, which highlights their core role in the heat stress response. The unique temporal responses to heat stress in heat-resilient and heat-sensitive cultivars provides a foundation for understanding heat stress resilience during the reproductive stage.